Microplastic Pollution: Exploring the Role of Social Class on Awareness, and Exposure - Papadopoulos, Hari (Pusat Riset dan Inovasi Nasional, 2026)
This research examines the complex relationship between social class and awareness of microplastic pollution, revealing that socioeconomic status alone cannot fully explain variations in public understanding and concern. Although previous studies often associate lower socioeconomic groups with higher environmental vulnerability, the findings of this study derived through qualitative methods, literature reviews, and interviews show that the link is far more nuanced. Factors such as access to credible information, quality of environmental education, cultural habits, and community-level norms play equally significant roles in shaping individuals’ perceptions and behaviors toward microplastic pollution. The results indicate that addressing microplastic pollution requires more than single-dimension solutions focused solely on socioeconomic disparities. Instead, a multidimensional approach involving improved public education, policy reforms that promote environmental responsibility, and active community participation is essential. Only through the integration of these elements can efforts to mitigate microplastic pollution become more effective and sustainable across in different social groups.